2006
DOI: 10.1002/eji.200635993
|View full text |Cite
|
Sign up to set email alerts
|

Early type I interferon‐mediated signals on B cells specifically enhance antiviral humoral responses

Abstract: Type I interferons (IFN-I) limit viral spread by inducing antiviral genes in infected target cells and by shaping the adaptive response through induction of additional cytokines. Vesicular stomatitis virus (VSV) efficiently triggers the production of IFN-I in mice, and it is suggested that IFN-a is induced after binding of VSV to TLR7 in infected cells. Our study with virus-specific B cell receptor-transgenic mice demonstrates here that IFN-I directly fuel early humoral immune responses in vivo. VSV-specific B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
99
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 44 publications
9
99
2
Order By: Relevance
“…In vivo evidence for a direct IFN-mediated role in B cell regulation has come from three recent studies. We provided evidence for direct IFN-mediated B cell stimulation to enhance virusspecific B cell responses to influenza virus infection (8), and similar findings were reported by Fink et al (28) The study presented here was conducted to more precisely define the nature of the innate signals that drive early local B cell activation during influenza infection and to determine the extent to which these stimuli modulate B cell responsiveness. Our data show that local secretion of type I IFN is the major innate signal stimulating respiratory tract B cells.…”
supporting
confidence: 85%
“…In vivo evidence for a direct IFN-mediated role in B cell regulation has come from three recent studies. We provided evidence for direct IFN-mediated B cell stimulation to enhance virusspecific B cell responses to influenza virus infection (8), and similar findings were reported by Fink et al (28) The study presented here was conducted to more precisely define the nature of the innate signals that drive early local B cell activation during influenza infection and to determine the extent to which these stimuli modulate B cell responsiveness. Our data show that local secretion of type I IFN is the major innate signal stimulating respiratory tract B cells.…”
supporting
confidence: 85%
“…Assuming the presence of Ͼ10 9 B cells in a mouse, basically all of which are IFNAR deficient (3, 10), Ͻ0.1% of the B cells can theoretically get infected upon injection of 2 ϫ 10 6 PFU VSV. Because, in absence of IFNAR, VSV-specific B cells do not seem to get preferentially infected (15), this would result in the infection and destruction of Ͻ0.1% of the VSV-specific B cell repertoire. Thus, the observations described in this work probably reflect the in vivo conditions more appropriately than adoptive transfer experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, IFNAR Ϫ/Ϫ mice, which showed a reduced frequency of influenza-specific B cells, produced a changed isotype pattern of influenza-specific Abs, and the differentiation of activated B cells to Ab-secreting plasma cells was hampered (14). Recent VSV infection studies conducted in mice carrying adoptively transferred transgenic VSV-specific B cells suggested that IFNAR signaling of B cells enhanced plasma blast formation and increased IgM responses (15). However, in these studies, the adoptively transferred IFNARdeficient B cells expressing a transgenic BCR competed with endogenous IFNAR-competent B cells.…”
mentioning
confidence: 99%
“…32 Gene expression analysis of collagen and 18S RNA was performed using kits from Applied Biosystems (Foster City, CA). For analysis, the expression levels of all target genes were normalized against 18S rRNA or GapDH mRNA (⌬Ct).…”
Section: Mrna Gene Profiling By Quantitative Rt-pcrmentioning
confidence: 99%
“…32 In brief, cells were stained for 15 minutes with tetramers at 37°C followed by incubation with the antibodies anti-CD8, anti-CD69, anti-CTLA4, anti-CD62L, or anti-CD44 (BD Bioscience, Franklin Lakes, NJ) or the antibodies anti-PD-1 or anti-IL-7R␣ (eBioscience, San Diego, CA). To measure intracellular IFN-␥ production, splenocytes were incubated with peptide for 6 hours at 37°C, for the last 5 hours with 1 mg/L Brefeldin A (Sigma-Aldrich, St Louis, MO), then stained for CD8 at 4°C.…”
Section: Fluorescence-activated Cell Sorting Analysismentioning
confidence: 99%